Parental beliefs about social withdrawal in preschool age - Greco, Carolina (2022)
Background: Parental beliefsnamely, parents’ ideas, knowledge, values and attributions are essential in the study of relationships between parents and children. They consist of cognitive and affective processes that influence strategies to promote acceptable social behaviors or to modify those considered undesirable. General Objective: To explore fathers’ and mothers’ beliefs about their children’s social withdrawal behaviors in the city of Mendoza, Argentina. Method: A qualitative methodology and a grounded theory approach were chosen. A non probability purposive sampling was used. Fathers and mothers of five four-year-old children who attended public educational institutions participated in the study. The focused interview was used as data collection instrument. Results: Emerging categories: internal and external causal attributions, causal attributions of cognitive and/or social emotional development, parental socialization strategies characterized by excessive control and overprotection. Conclusions: Parental beliefs provide a frame of reference that guides children’s interactions and determines the opportunities parents offer their children for their social emotional development. Authorship contributionCG, KNC and MSI: all authors participated in writing and revising the manuscript in drafting and revising the manuscript.